Counter- and co-directed swirling-type waves due to orbital excitations of a square-base tank - Lagodzinskyi, O.E.; Timokha, A.N. (Reports of the National Academy of Sciences of Ukraine, 2021)
The analytic technique and numerical experiments are employed to show that the orbital elliptic translational ex citations of a square-base container can, depending on the ratio of the semiaxes of the elliptic orbit, lead, when the forcing frequency is close to the lowest natural sloshing frequency, to both the counter- and co-directed (relative to the orbital forcing direction) stable swirling-type steady-state resonant waves. For a non-zero damping in the hydrodynamic wavy system, the passage to circular orbits makes the stable counter-directed swirling impossible.